2020
DOI: 10.1002/fsn3.1574
|View full text |Cite
|
Sign up to set email alerts
|

Development of sorghum‐based shortbread biscuits from “muskwari” flour

Abstract: In order to produce biscuits from off‐season sorghum, a local “Muskwari” sorghum was milled and sieved. This flour was used to produce shortbread biscuits with different substitutions rates of wheat flour to that of sorghum. The standard formulation of this same type of shortbread biscuits was used and biscuits were produced with incorporation rates of wheat flour to that of sorghum, from 0% to 100%, with a gap of 10 between two consecutives percentages. The technological characterization of the sorghum flour … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The ash decreases around 3 values with the addition of PSP flour ranging from 85-90 gr, because an increase in PSP flour does not have a significant effect on the ash content of the biscuits. Ash is an element of minerals or inorganic substances contained in food (Monti, Virgilio, & Ventury, 2018;Darman, Sidoine, & Lendzemo, 2020).…”
Section: Moisture and Ashmentioning
confidence: 99%
“…The ash decreases around 3 values with the addition of PSP flour ranging from 85-90 gr, because an increase in PSP flour does not have a significant effect on the ash content of the biscuits. Ash is an element of minerals or inorganic substances contained in food (Monti, Virgilio, & Ventury, 2018;Darman, Sidoine, & Lendzemo, 2020).…”
Section: Moisture and Ashmentioning
confidence: 99%
“…Although sorghum is still one of the underutilized crops, new studies have expanded to include sorghum-based food items aimed for human consumption ( 7 ). Darman et al ( 18 ), for example, examined the nutritional composition of sorghum-based biscuits and reported considerable levels of carbohydrates, dietary fiber, and energy. Another study reported improved chemical, functional, and nutritional properties of sorghum-based snacks fortified with mung bean ( 19 ).…”
Section: Introductionmentioning
confidence: 99%